Stakeholders’ participation in regional energy planning processes. Case study from RES H/C SPREAD project - Faberi, Stefano (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The article briefly describes, through the illustration of four best practices, a successful experience concerning the involvement of external stakeholders in the realization of regional energy plans for the fostering of the renewable energy technologies for heating and cooling in different EU countries. This participatory activity was carried out within the RES H/C SPREAD project (EU Intelligent Energy Program 2014-2016). Project objective was to strengthen the capacity of regional and local authorities for planning in a sustainable development framework.